Synergistically optimizing interdependent thermoelectric parameters of n-type PbSe through alloying CdSe. Issue 6 (15th May 2019) - Qian, Xin; Wu, Haijun; Wang, Dongyang; Zhang, Yang; Wang, Jinfeng; Wang, Guangtao; Zheng, Lei; Pennycook, Stephen J.; Zhao, Li-Dong
Abstract : CdSe alloying can flatten the conduction band, enlarge the band gap, and suppress the bipolar thermal conductivity of PbSe. Abstract : PbSe is an alternative of the well-known moderate-temperature thermoelectric material PbTe, and has attracted much attention because of its advantages of high earth-abundance and low price of Se compared with Te. To enhance the thermoelectric performance of PbSe, its several shortcomings should be overcome, such as poor electrical conductivity, small Seebeck coefficient and bipolar thermal conductivity. Simultaneously improving these properties is a big challenge in the thermoelectric community. In this work, we successfully addressed these problems with PbSe by introducing just one component, CdSe, which has a similar crystal structure and larger band gap compared to PbSe. The introduction of CdSe realizes four positive effects: (1) improving the effective mass through flattening the conduction band; (2) decreasing the lattice thermal conductivity enormously by introducing hierarchical sub-nano defects; (3) keeping a high carrier mobility due to the nanostructure-free matrix; (4) suppressing the bipolar thermal conductivity via enlarging the band gap of PbSe. Due to all the above synergistically optimized electrical and thermal transport properties, a superior ZT value of ∼1.4 and ZT ave of ∼0.7 are achieved in n-type PbSe through CdSe alloying, and the calculated conversion efficiency can reach 10.5%. Our results indicate that PbSe is a robust candidate for medium-temperature thermoelectric applications.